Analysis of the Processing Practices of Rubber Latex by the Small Holders in Alathur Taluk - Sasi M K (Department of Plantation Crops and Spices, College of Horticulture, 1994)
A study was conducted among small holders of Alathur taluk to understand the extent of adoption of scientific processing techniques by the rubber growers. One hundred holdings, representing different geographical regions in the taluk and different size groups were selected and the farmers as well as the tappers were interviewed with the help of a questionnaire.